Navigating Borders : Inside Perspectives on the Process of Human Smuggling into the Netherlands - van Liempt, Ilse (Amsterdam University Press, 2007)
Navigating Borders into the Netherlands provides a unique in-depth look at human smuggling processes. Based on biographical interviews with smuggled migrants in the Netherlands, the study reveals considerable differences that exist in smuggling's underlying causes, how journeys evolve, and outcomes of the process. This research from an insider's perspective clearly demonstrates that smuggled migrants are not passive actors, there is a broad variety in types of smugglers, and interactions between migrants and smugglers largely determine how the smuggling process evolves.
Dit boek geeft een een boeiend inzicht in mensensmokkel. Gebaseerd op biografische interviews met gesmokkelde migranten in Nederland, laat de studie zien dat onderliggende oorzaken, de manier waarop de reis plaatsvindt alswel de uitkomst van mensensmokkelprocessen aanzienlijk kunnen verschillen. Door een perspectief van binnenuit te kiezen wordt het duidelijk dat gesmokkelde migranten geen passieve rol spelen. Verder valt op dat er verschillende type smokkelaars zijn en dat de interacties tussen die twee voor een belangrijk gedeelte het verloop van het proces bepalen.
English
Keywords: Ethnic studies; Science: general issues; human smuggling; irregular migration; netherlands; horn of africa; fortress europe; wetenschap algemeen; asylum; forced migration; popular science; former soviet union; iraq; transit migration